Faktor Penentu ROA PT Bank Syariah Indonesia Tbk: BOPO, FDR dan NPF Tahun 2021-2025 - Rizqina Faraaj; Alfaridzi Akasyah; Yani Aguspriyani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the determinants of Return on Assets (ROA) at PT Bank Syariah Indonesia Tbk (BSI) during 2021–2025, focusing on Operational Expense to Operational Income (BOPO), Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF). After the 2021 merger of state-owned Islamic banks, BSI experienced rapid growth within Indonesia’s sharia banking industry, supported by risk-sharing principles and increasing public demand. However, profitability fluctuations remain influenced by operational efficiency, liquidity management, and financing risk. Previous studies generally found BOPO negatively affects ROA, FDR produces mixed results, and NPF reduces profitability, yet few studies specifically examine BSI’s post-merger condition. This research applies a quantitative explanatory method using secondary time-series data from BSI’s audited financial reports. Data were analyzed using multiple linear regression in Stata after classical assumption tests, including stationarity through the Augmented Dickey-Fuller test. The regression model produced ΔROA = -0.000357ΔFDR - 0.073418ΔBOPO - 0.143822ΔNPF + ε with F-statistic 148.19 (p=0.000) and R²=0.9674. The findings show BOPO has a significant negative effect on ROA, indicating operational efficiency as the main determinant of profitability. Meanwhile, FDR and NPF have negative but insignificant effects, reflecting relatively effective liquidity and risk management. Therefore, BSI should strengthen efficiency through digitalization and cost control strategies